PERAN KOMISI PEMILIHAN UMUM ( KPU ) SANGATTA KABUPATEN KUTAI TIMUR DALAM MENGURANGI POTENSI TINDAK PIDANA PEMILU YANG MERUJUK PADA UNDANG – UNDANG NOMOR 15 TAHUN 2011 - Susanti Pratiwi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT                Election city of East Kutai Regency Sangata is still less effective due to its implementation there are still violations that benefit organizations or certain parties. Organizers election itself is an institution that organizes election consisting of the election commission and the election supervisory body as a unity function administration of elections to choose members of the house of representatives, the regional representative council and the regional representatives council. Election commission, hereinafter referred to as the commission, is an institution election which is national, permanent, and independent charge of carrying out election and the election supervisory body, hereinafter referred to as Bawaslu, is the agency charged with overseeing the election organizers administration of elections in the entire territory of the Republic of Indonesia. in article 8 of Law No. 15 of 2011 tasks and authority of the Commission is very strong. Election law is a set of rules that aims to ensure elections run in accordance with the principle of election: direct, general, free, confidential, honest and fair. Operationally, the election law to prevent and impose sanctions in order to prevent violations of election rules. Election criminal offense is a violation of the criminal provisions of the election as stipulated in the electoral law